A private chapter of the war. - Bailey, George W. (G.I. Jones and company, 1880)
This volume, which is to select from the whole military history a "private chapter," and present it as worthy of being recorded as uncommon experiences. It presents a limited inside view of a portion of the Confederacy within its military lines, as secretly observed by a "stray" from the invading army in blue, whose experiences disclose the real political sentiments of fair samples of different classes who resided within the Confederacy during the war, experiences, not of a spy, not of a scout, but of a harmless escaped prisoner of war. A refugee; free, yet practically imprisoned; escaped, y et practically confined within broader limits only; guilty of no offence but that of performance of duty in resorting to all proper means and expedients, and promptly taking advantage of all circumstances and occasions, in determined persistent efforts to regain the Federal lines.--taken from introductory
This volume, which is to select from the whole military history a "private chapter," and present it as worthy of being recorded as uncommon experiences. It presents a limited inside view of a portion of the Confederacy within its military lines, as secretly observed by a "stray" from the invading army in blue, whose experiences disclose the real political sentiments of fair samples of different classes who resided within the Confederacy during the war, experiences, not of a spy, not of a scout, but of a harmless escaped prisoner of war. A refugee; free, yet practically imprisoned; escaped, y et practically confined within broader limits only; guilty of no offence but that of performance of duty in resorting to all proper means and expedients, and promptly taking advantage of all circumstances and occasions, in determined persistent efforts to regain the Federal lines.--taken from introductory
Keywords: United States / History / Civil War, 1861-1865 / Prisoners and prisons; United States / History / Civil War, 1861-1865 / Personal narratives; Récits personnels. / rvmgf; Personal narratives / lcgft; Personal narratives / fast / (OCoLC)fst01423843; History / fast / (OCoLC)fst01411628